Multiple-Dose Up-Titration Study to Evaluate the Safety, Tolerability, Pharmacokinetics, and Pharmacodynamics of Selexipag, an Orally Available Selective Prostacyclin Receptor Agonist, in Healthy Subjects - Bruderer, Shirin; Hurst, Noémie; Kaufmann, Priska; Dingemanse, Jasper (Pharmacology, 2014)
Objective: The objective of this study was to assess the safety, tolerability, pharmacokinetics, and pharmacodynamics of selexipag, an orally available selective prostacyclin receptor agonist, in development for pulmonary arterial hypertension in healthy subjects. Methods: This was a double-blind, placebo-controlled, randomised, multiple-ascending-dose, up-titration study. Male subjects received increasing oral doses of selexipag (400-1,800 µg; n = 12) or placebo (n = 4) twice daily for 3 days each, using incremental steps of 200 µg between each dose level. Standard safety and tolerability data were collected. Blood samples were taken to assess the pharmacokinetics of selexipag and its active metabolite ACT-333679 and possible effects on platelet aggregation. Results: Dose levels of selexipag up to 1,600 μg were well tolerated and this dose was identified as the maximum tolerated dose. Plasma exposure to ACT-333679 was approximately 4 times higher than that to selexipag. Steady-state conditions for both compounds were reached on day 3 of each dose level, and no accumulation of selexipag or ACT-333679 was observed. Based on the area under the curve and the maximum plasma concentration, the pharmacokinetics of selexipag and ACT-333679 were dose proportional. At the highest dose level, the geometric mean terminal half-life of selexipag and ACT-333679 was 1.4 and 8.7 h, respectively. The observed effects on platelet aggregation were variable without obvious drug- or dose-dependent pattern. Conclusions: Oral administration of increasing doses of selexipag was well tolerated. The present results support the conduct of future clinical trials.